Hakikat Filsafat Ilmu Dalam Pelayanan Publik Pada Pemerintahan Daerah - Julharya Adrika; Azmi Fitrisia; Ofianto Ofianto (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Service ethics is the use of noble values by service personnel in providing public services. The services provided to the community are based on predetermined rules, namely legal and social norms. The application of service ethics must be a means of control for service personnel when carrying out their duties and functions and authority in administering public services to the people in the regions. Public service is an activity or a series of activities in the context of fulfilling the service needs of every citizen and resident for goods, services, and/or administrative services provided by the organizers. Apparatuses who have ethics in acting and behaving daily within the scope of regional government will always be moved to defend the honor of the government in carrying out their duties and functions as well as possible and will always try to avoid violations that will undermine the authority of the organizational unit or government where they are assigned